The Binding of Diiodosalicylate and Flufenamate to the Plasma Antiactivator: Analysis of Chemical Fibrinolysis - Nanninga, L B (Thrombosis and Haemostasis, 1979)
The fibrinolytic effect of diiodosalicylate was expressed as apparent units urokinase. The dissociation constant of the urokinase-inhibitor complex is increased 19 times in the presence of 10-2 M diiodosalicylate. The binding of diiodosalicylate to the antiactivator was estimated and the increase in free urokinase in the presence of diiodosalicylate was calculated. With 10-2 M diiodosalicylate present only 4% of the inhibitor remains free to bind urokinase. Therefore, the fibrinolytic action of diiodosalicylate can be explained on the basis of its binding to the inhibitor and the release of free urokinase.